Validation of an instrument to determine sedentary behaviors in university students - Méndez Ávila, Julio César (2021)
Objective: To validate a data collection instrument to determine sedentary behaviors in university students. Method: The research was conducted through a sequential exploratory mixed type design (DEXPLOS), with a qualitative and a quantitative stage. For the qualitative stage, the focus group technique was used in which 24 students participated with a semi-structured interview guide that was subjected to a review by five experts and was analyzed with the ATLAS TI 8 program. Later, in the quantitative stage, a sampling by conglomerates dividing the population from 1st to 10th semester, obtaining a sample of 200 students from the careers of Nursing, Physiotherapy and Physical Education and Sports Sciences. Based on this, an own questionnaire was developed with a Likert scale with 7 response options and the SPSS version 25 program was used for the analysis of quantitative data. Main results: For the qualitative stage, three categories were found that contextually encompass the activities carried out in daily life by university students: lifestyle, physical activity and free time. For the quantitative stage, the instrument had a validation of the Cronbach's Alpha coefficient of 0.780 and Guttman's coefficient of 0.751. General conclusion: The questionnaire proposed in this study is adequate to estimate in an objective and contextualized way behaviors and habits in Queretaro university students since it has a reliability above the established limit.